1992
DOI: 10.1093/oxfordjournals.eurheartj.a060224
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocardiographic non-invasive localization of accessory pathways in the Wolff-Parkinson-White syndrome by a multichannel system

Abstract: Electrical activity can be localized by magnetocardiography (MCG) non-invasively. In this study a 37-SQUID (Super Conducting Quantum Interference Device) sensor multi-channel system (KRENIKON) was used to assess the potential of magnetocardiography to localize accessory pathways with a multichannel system. Seven WPW patients were studied by means of magnetocardiography. Prior to the MCG recordings, the site of the accessory pathway had been determined in all patients by invasive catheter mapping. MR images of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Although MCGs have unique fundamental principles, can be quantified using absolute scales [4] , and are less affected by the body tissues compared with 12-lead electrocardiograms (ECGs) [5] , their clinical utility has not been established. Several reports have described MCGs studies of His potentials [6,7] , ventricular repolarization abnormalities during sinus rhythm [8][9][10] , and arrhythmic foci in patients with premature contractions or Wolff-Parkinson-White syndrome [11][12][13][14] . However, there are very few MCG studies of reentrant arrhythmias.…”
Section: Introductionmentioning
confidence: 99%
“…Although MCGs have unique fundamental principles, can be quantified using absolute scales [4] , and are less affected by the body tissues compared with 12-lead electrocardiograms (ECGs) [5] , their clinical utility has not been established. Several reports have described MCGs studies of His potentials [6,7] , ventricular repolarization abnormalities during sinus rhythm [8][9][10] , and arrhythmic foci in patients with premature contractions or Wolff-Parkinson-White syndrome [11][12][13][14] . However, there are very few MCG studies of reentrant arrhythmias.…”
Section: Introductionmentioning
confidence: 99%
“…However, in 1998, using the Helsinki multichannel system with an acceptable signal-to-noise ratio, Fenici et al demonstrated that MCG is an effective clinical tool for non-invasive threedimensional electro-anatomical imaging [41]. Accurate localization of the accessory pathway has been successfully performed in patients with Wolf-ParkinsonWhite (WPW) syndrome [42][43][44][45][46]. In these studies the accuracy of the non-invasive MCG localization of arrhythmogenic substrates has been evaluated by comparison with the results of conventional invasive catheter mapping.…”
Section: Rozkład Prądów Nasierdziowych U Pacjenta Z Ciasnym Zwężenimentioning
confidence: 99%
“…Since superconducting multi-channel systems have become available, the cardiac magnetic field can be recorded with great sensitivity simultaneously from a number of positions over the chest (Pasquarelli andDi Luzio1993, Tavarozzi et al 2002a), hence allowing accurate field mapping during the cardiac cycle, useful for several clinical applications, particularly for arrhythmias (Weismuller et al 1992, Brockmeier et al 1997, Muller et al 1999, Hren et al 1999, Kandori et al 2001, Comani et al 2001, 2004a, Tavarozzi et al 2002b.…”
Section: Introductionmentioning
confidence: 99%